Asparagine, valine, and threonine in the third extracellular loop of muscarinic receptor have essential roles in the positive cooperativity of strychnine-like allosteric modulators - Jakubík, J; Krejcí, A; Dolezal, V (The Journal of pharmacology and experimental therapeutics, 2005)
We have investigated allosteric interactions of four closely related strychnine-like substances: Wieland-Gumlich aldehyde (WGA), propargyl Wieland-Gumlich aldehyde, strychnine, and brucine with N-methylscopolamine (NMS) on M(3) subtype of muscarinic receptor genetically modified in the second or the third extracellular loop to corresponding loops of M(2) subtype (M(3)o2 and M(3)o3 chimera). The M(3)o2 chimeric receptor The exhibited no change in either affinity of strychnine, brucine, and WGA or in cooperativity of brucine or WGA, whereas both parameters for propargyl-WGA changed. In contrast, there was a change in affinity of all tested modulators (except for brucine) and in their cooperativity in the M(3)o3 chimera. Directions of affinity changes in both chimeras were always toward values of the donor M(2) subtype, but changes in cooperativity were variable. Compared with the native M(3) receptor, strychnine displayed a slight increase in positive cooperativity and propargyl-WGA a robust decrease in negative cooperativity at M(3)o2 chimera. Similar changes were found in the M(3)o3 chimera. Interestingly, cooperativity of brucine and WGA at the M(3)o3 chimera changed from negative to positive. This is the first evidence of constitution of positive cooperativity of WGA by switching sequences of two parental receptors, both exhibiting negative cooperativity. Gradual replacement of individual amino acids revealed that only three residues (NVT of the o3 loop of the M(2) receptor) are involved in this effect. Data suggest that these amino acids are essential for propagation of a conformation change resulting in positive cooperativity induced by these modulators.
Keywords: Molecular Sequence Data; Protein Structure, Tertiary; sekvence aminokyselin; Strychnine; strychnin; Protein Binding; Cercopithecus aethiops; extracelulární prostor; Valine; receptory muskarinové; Mutagenesis, Site-Directed; Threonine; valin; Extracellular Space; COS buňky; Receptors, Muscarinic; Allosteric Regulation; mutageneze cílená; threonin; Asparagine; zvířata; Humans; Amino Acid Sequence; vazba proteinů; alosterická regulace; Chlorocebus aethiops; molekulární sekvence - údaje; asparagin; terciární struktura proteinů; COS Cells; lidé; Animals